P107. Physiological mechanisms of cerebellar transcranial direct current stimulation in humans. Issue 8 (August 2018) - Batsikadze, G.; Nitsche, M.; Herlitze, S.; Timmann, D.
Abstract : Background: Recently, transcranial direct current stimulation (tDCS) became a popular method to non-invasively modulate cerebellar excitability and help us broaden our understanding of cerebellar functions and introduce new therapeutic applications. Despite its popularity, its parameters, such as current polarity, stimulation intensity and electrode positions to induce specific effects have not yet been standardized. We aimed (1) to test the effects of tDCS with different electrode montages (see below) on cerebellar-brain inhibition (CBI) and (2) to explore the effect of tDCS on specific cerebellar-brain connections measured by the CBI recruitment curve (CBI-RC). Methods: 15 and 14 young and healthy participants took part in Experiments 1 and 2, respectively. In all experiments, the target tDCS electrode was placed over the right cerebellar cortex. In Exp. 1, the return electrode over one of the following three positions: the right buccinator muscle, the left supraorbital area or the right deltoid muscle and in Exp. 2, it was positioned over the right buccinator muscle. CBI was measured by double-TMS protocol, with the conditioning stimulus (CS) over the right cerebellum with an intensity of 5% below the brainstem motor threshold (BMT) followed by the test pulse over the left primary motor cortex 5 ms later. For CBI-RC, five different CS intensities were used (−5%, −10%, −15%, −20%, −25% below BMT). The after-effects of 2 mA anodal or cathodal cerebellar tDCS on CBI or CBI-RC in Exp. 1 and 2, respectively, were measured before and for two hours after 15 min of tDCS. Results: In Exp. 1, both tDCS polarities significantly decreased CBI for at least two hours compared to both sham and pre-stimulation values. No significant differences between different return electrode positions were observed. In Exp. 2, CBI was significantly increased after anodal and was decreased after cathodal tDCS with low CS intensities in a polarity-specific manner. Conclusions: In accordance with the results reported by many studies, our results suggest that the return electrode positioning has no significant impact on the tDCS after-effects. The results of Exp. 2 show that the recruitment of the cerebellar-brain connections varies depending on tDCS polarity and CS intensity, suggesting that tDCS differently affects neurons in different layers of the cerebellar cortex. This polarity-specific dependence should be considered for tDCS applications and addressed in future studies. Funded byMercur Pr-2015-0010 and SFB1280 (TP A05 and A06).